Ophrys apifera Huds. (Orchidaceae) on a heap of limestone mine waste – the first population found in the Sudetes and the second in Poland - Wójcicka-Rosińska, Anna; Rosiński, Dariusz; Szczęśniak, Ewa (Biodiversity: Research and Conservation, 2020)
The paper reports the finding of a new locality of Ophrys apifera – the first locality of this species in the Sudeten range and the second in Poland. A new population was found in the Kaczawskie Mts. (Western Sudetes). It consists of 23 flowering plants and occurs in an operating limestone quarry. The detailed data on this population and its habitat are included.